2014
DOI: 10.1155/2014/496146
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Physical Properties of Sintered Alumina in the Presence of MgO Nanopowder

Abstract: Magnesium oxide nanopowder is synthesized using magnesium nitrate hexahydrate and oxalic acid as precursors via the sol-gel method. In order to investigate the effect of magnesia nanopowders on the physical properties of sintered alumina, 0.1, 0.3, and 0.5 wt% of MgO are added to alumina. The prepared specimens were sintered at 1570 ∘ C for 4 hours under an inert atmosphere. The morphology and size of nanopowders were characterized by transmission electron microscope (TEM) and scanning electron microscope (SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…It is interesting to note that the observed new grains in this study is contrary to the reported alumina final grain size of 2.6 mm sintered at 1570°C for 4 h by conventional thermal sintering [21]. Therefore, result obtained in this study shows that using CSP under specified conditions, a polycrystalline material with preserved or controlled crystallite sizes could be achieved as reported in a related study [19].…”
Section: Resultscontrasting
confidence: 76%
“…It is interesting to note that the observed new grains in this study is contrary to the reported alumina final grain size of 2.6 mm sintered at 1570°C for 4 h by conventional thermal sintering [21]. Therefore, result obtained in this study shows that using CSP under specified conditions, a polycrystalline material with preserved or controlled crystallite sizes could be achieved as reported in a related study [19].…”
Section: Resultscontrasting
confidence: 76%
“…This process improves the quality of sintered alumina. 24 Magnesia-doped alumina has good strength, hardness and improved toughness. 25 Yttria-doped zirconia is a solid electrolyte for fuel cell applications.…”
Section: Halogens As Mineralizersmentioning
confidence: 99%
“…Furthermore, we evaluate the effects of magnesium addition on the microstructural and compositional features of the resulting materials. The rationale behind the introduction of magnesium is based on the reported positive effect of MgO on the densification of alumina, improving the mechanical properties of alumina even at low additions (< 0.25 %) [26][27][28]. With respect to iron aluminides, we hypothesize that a correspondingly positive effect on the formation of the alumina scale, which is responsible for the excellent corrosion stability, can be achieved by introducing magnesium as a precursor to MgO under application conditions.…”
Section: Introductionmentioning
confidence: 99%